Comprehensive proteomic characterization of pulmonary arterial hypertension in Chinese people - Liu, Tianya; Zhou, Siqi; Wang, Rui; Xu, Xiaomei; Gao, Fang; Zu, Jie; Wang, Zhiping (Frontiers in Molecular Biosciences, 2025)
BackgroundPulmonary arterial hypertension (PAH), a serious disease, is characterized by various degrees of pulmonary vascular remodeling, inflammation, and increased vascular resistance, leading to fatalities in patients with severe conditions. However, the molecular mechanisms underlying the pathogenesis of PAH remain incompletely understood.MethodsRNA sequencing (RNA-seq), 4D label-free proteomics, and phosphoproteomics were employed to detect the levels of mRNA, proteins, and phosphorylation modification in the lung tissues of PAH patients, compared to those in the control group. Parallel reaction monitoring (PRM) was subsequently performed to verify the differentially expressed proteins (DEPs) identified by proteomic profiling.ResultsAfter data filtering (|log2FoldChange| > 1 and p < 0.05), the PAH group exhibited 967 differentially expressed genes (DEGs), 764 DEPs, and 411 phosphorylated DEPs compared with those of the control group. By integrating transcriptomic and proteomic analyses, 54 proteins were identified with consistent changes at both levels. We analyzed several proteins using PRM, including known candidates such as enolase 1 (ENO1) and chloride intracellular channel 1 (CLIC1), as well as novel proteins such as caveolin-2 (CAV2) and eukaryotic translation initiation factor (EIF2A). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses of DEPs showed significant enrichment of biological processes associated with inflammatory response, oxidative stress, and tissue remodeling. Phosphorylated DEPs showed significant enrichment in key pathways, including autophagy, apoptosis, and hypoxia inducible factor (HIF) signaling, all of which were closely associated with PAH.ConclusionDysregulated pathways such as autophagy, apoptosis, and HIF-1 signaling, along with altered genes or proteins, contribute to PAH by inducing pulmonary vascular remodeling and chronic vasoconstriction. These findings may facilitate the discovery of novel therapeutic targets and effective treatment strategies for PAH.